THE QUANTIFIED RUNNER’S KNEE: A SOCIO-TECHNICAL REVIEW OF ILIOTIBIAL BAND DYNAMICS, DIGITAL DIAGNOSTICS, AND REGENERATIVE INNOVATION - Dawid Głaz,; Łukasz Deska,; Szymon Zysiak,; Maksymilian Głaz,; Natalia Kamińska,; Jędrzej Zaguła,; Wojciech Sołtys,; Cezary Kosmecki,; Mateusz Stronczyński,; Kacper Wicha, (International Journal of Innovative Technologies in Social Science, 2025)
The global proliferation of recreational running has evolved from a simple health behavior into a complex socio-technical phenomenon, deeply embedded in the digital economy. While the "running boom" has yielded cardiovascular benefits, it has precipitated an epidemic of musculoskeletal injuries, notably Iliotibial Band Syndrome (ITBS) and Patellofemoral Pain (PFP). Traditionally viewed through a reductionist biomedical lens, the etiology of these injuries is increasingly mediated by technological factors—from "quantified self" metrics driving training loads to Artificial Intelligence (AI) in diagnostics. This review synthesizes biomechanical evidence linking iliotibial band tension to Chondromalacia Patellae (CMP) via Lateral Patellar Compression Syndrome (LPCS) and integrates this into a sociological framework. We examine how wearable technology creates a "paradox of data" that may exacerbate overuse injuries. Furthermore, we evaluate the economic burden on healthcare systems and workforce productivity. Finally, we propose an integrated therapeutic model combining biomechanical correction with regenerative medicine (mesenchymal stem cells) and digital health interventions. This interdisciplinary review argues that effective injury management requires a convergence of orthopedic precision and sociological insight.